Effect of pysical filters (aluminum 0.2mm and o.jmm thick) on sensitivity, uniformity, and spatial resolution of Toshiba GCA- 901A/HG gamma camera with tc-99m in planar imaging - Nawi, Siti Nazipah Mohamad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2004)
The performance of a scintillation-camera system is assessed to assure the acquisition of diagnostically reliable images. Decisions-making data to determine acceptability of camera performance are acquired when some parameters are tested. So, in this study the sensitivity, uniformity and system spatial resolution parameters are tested by using physical filters, aluminum 0.2 mm and aluminum 0.3 mm. The Tc-99m is used as a source. Two collimator are used which are low energy parallel-hole collimators, i.e. low energy high resolution (L.E.H.R) and low energy general purpose (L.E.G.P.). The reason for this choice was that these collimators are the most commonly used for clinical studies in nuclear medicine departments. For data acquisition, the method utilizes a photopeak energy window ranging 126 keV-154 keV ofTc-99m spectrum with 128 x 128 matrix size were used for all tests. From sensitivity, uniformity, and spatial resolution results material filtered data shows an improvement.